Socialization pattern (Paguyuban family child education study) in Malino Gowa - Syamsuddin. AB, Syamsuddin. AB (Technium Social Sciences Journal, 2021)
Research on the socialization of children’s education aims to analyze the social actions taken by the association family on the implementation of patterns carried out before and after child birth. This type of descriptive qualitative research is because it can guide researchers to obtain new findings, the data sources for the father and mother are 4 people with 2 families (main informants), and 1 community leader (expert informant) the number of informants is 7 people. The research instrument of the researchers themselves, in-depth interview data collection, observation, documentation, with data analysis model miles and huberman, namely data reduction, data presentation drawing conclusions. The results showed that the pattern of socialization of children’s education by parents varied greatly, namely (a). The period of pregnancy; parents maintain nutritious food during pregnancy and speak and act well, (b). Give breast milk, (c). Immunization, (d). Home environment or atmosphere, (e) Manners, (f). Discipline; religious values are still instilled in children. Novelti; sacrifice of parents in the socialization of children’s education but parents are elevated with dignity for the success of their children.